Technological aspects of the production of fructo and Galacto-Oligosaccharides. Enzymatic Synthesis and Hydrolysis - Martins, Gonçalo N. (2019)
Fructo- and galacto-oligosaccharides (FOS and GOS) are non-digestible oligosaccharides with prebiotic properties that can be incorporated into a wide number of products. This review details the general outlines for the production of FOS and GOS, both by enzymatic synthesis using disaccharides or other substrates, and by hydrolysis of polysaccharides. Special emphasis is laid on technological aspects, raw materials, properties, and applications.